Factors Influencing Human Capital in Ready Made Garments Industry in Bangladesh - Kamal, Md Aktar (Journal of Social Economics Research, 2019)
The aim of this research is to determine the factors that influence the human capital of an organisation. An investigative study has been used to observe an exploratory factor analysis (CFA) of human capital. This study has been undertaken on the Ready-Made Garment (RMG) industry in Bangladesh and includes responses from 300 garment organisations using the cluster sampling technique. IBM, SPSS, and AMOS softwares were used to carry out the statistical analysis. The results suggest that skills, education and training, knowledge and competencies, and the attitudes of employees are very important elements of human capital. This study provides empirical evidence on the factors that affect human capital. It advises the policy maker to focus on key variables that affect the development of human capital in Bangladesh’s RMG industry. Bangladesh has a rapidly growing economy, currently maintaining above six percent annual growth in Gross Domestic Production (GDP), largely driven by the RMG industry.